Does water availability influence the abundance of species of the Phialocephala fortinii s.l. – Acephala applanata complex (PAC) in roots of pubescent oak (Quercus pubescens) and Scots pine (Pinus sylvestris)?. (April 2020) - Landolt, Maurus; Stroheker, Sophie; Queloz, Valentin; Gall, Anja; Sieber, Thomas N.
Abstract: The effects of irrigation on colonization of Pinus sylvestris and Quercus pubescens by members of the Phialocephala fortinii s.l. – Acephala applanata species complex (PAC) was assessed. Roots were collected from an irrigation experiment site. PAC species were identified based on 13 microsatellites. Irrigation and host species had a significant effect on the frequency of roots colonized by PAC. In oak ( Q . pubescens ) but not in pine ( P . sylvestris ), PAC were significantly more common on dry non-irrigated plots than on irrigated ones. Frequency of colonization of pine roots was twice as high as that of oak roots, and the mean number of PAC species per tree was significantly higher for pines. A hitherto unknown PAC species was found. The community structure was random except for the most frequently isolated Phialocephala europaea and Phialocephala helvetica, which inhibited one another in pine roots. The possible effects of PAC colonization on drought resistance of oak are discussed.